2016
DOI: 10.1148/radiol.2016160218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Management, and Natural Course of Incidental Findings on Brain MR Images: The Population-based Rotterdam Scan Study

Abstract: Purpose To present an updated prevalence estimate for incidental findings on brain magnetic resonance (MR) images and provide information on clinical relevance, including natural course, over a period of up to 9 years. Materials and Methods This study was approved by the institutional review board and all participants gave informed consent. In a prospective population-based setting, structural brain MR imaging was performed in 5800 participants (mean age, 64.9 years; 3194 women [55.1%]). Trained reviewers reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
109
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 25 publications
12
109
3
Order By: Relevance
“…The two major studies examining the prevalence of asymptomatic brain tumors in older populations are the Rotterdam study and the HUNT MRI study . The Rotterdam study was originally designed to identify risk factors for various chronic diseases (cardiovascular, endocrine, respiratory, etc.)…”
Section: Comparison Of Studies Examining the Prevalence Of Asymptomatmentioning
confidence: 99%
“…The two major studies examining the prevalence of asymptomatic brain tumors in older populations are the Rotterdam study and the HUNT MRI study . The Rotterdam study was originally designed to identify risk factors for various chronic diseases (cardiovascular, endocrine, respiratory, etc.)…”
Section: Comparison Of Studies Examining the Prevalence Of Asymptomatmentioning
confidence: 99%
“…In agreement, other studies in older populations have found significantly higher occurrences of IF. In observational studies, 32% (from a total of 700 participants, mean age 72.5 years), 7 9.5% (from a total of 5800 participants with a mean age of 64.9 years) 8 and 77.9% (from a total of 503 participants with a mean age of 75.3 years) 9 of asymptomatic participants presented with IF. Therefore, IF are commonly revealed in neuroimaging research, but their occurrence greatly differs between study populations.…”
mentioning
confidence: 99%
“…More than 70 years later, Cushing [13] and Dandy [14, 15] independently reported extensive series of cerebrovascular malformations, which were subsequently classified into distinct histopathological subtypes (telangiectasias, cerebral cavernous malformations, venous malformations, and arteriovenous malformations) [16, 17]. They occur with a high prevalence (estimated to be 4 - 6 % in earlier reports [18-20], but approximately 3% in recent population-based brain magnetic resonance imaging [MRI] studies [21]) around the globe in all ethnicities, and although they are most often sporadic, familial forms are not infrequent.…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%
“…CCM are common cerebrovascular lesions, also termed cavernomas, in the CNS and, rarely, the retina, with an estimated prevalence of 0.3-0.9%, on the basis of large prospective autopsy studies, clinically-based and population-based brain MR images [18, 21-29]. Cavernomas are collections of enlarged, densely packed vascular sinusoids with abnormal structure lined with a single layer of endothelial cells and lacking vessel wall elements, embedded in a collagen matrix without intervening brain parenchyma [16, 17].…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%